PENGEMBANGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS HYPNOTEACHING UNTUK MENGURANGI KECEMASAN MATEMATIKA SISWA - Lena Rosdiana Pangaribuan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics anxiety is one of the major factors affecting students' achievement, confidence, and participation in mathematics learning. Students with high levels of anxiety often experience difficulties in solving mathematical problems and tend to avoid challenging learning tasks. Therefore, an instructional model that integrates cognitive and psychological approaches is needed to create a more engaging and supportive learning environment. This study aimed to develop and evaluate a Problem Based Learning (PBL) model based on Hypnoteaching to reduce students' mathematics anxiety and improve their mathematical problem-solving skills. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The participants consisted of mathematics education experts, instructional design experts, mathematics teachers, and junior secondary school students. Data were collected through expert validation sheets, mathematics anxiety questionnaires, observations, interviews, and mathematical problem-solving tests. The data were analyzed using descriptive and inferential statistical techniques. The results showed that the developed model met the criteria of validity, practicality, and effectiveness. Students who learned through the PBL-Hypnoteaching model demonstrated lower mathematics anxiety, higher confidence, greater learning motivation, and better mathematical problem-solving performance than before implementation. The integration of problem-solving activities with relaxation, positive suggestion, affirmation, and reflective learning created a positive classroom atmosphere that encouraged active participation and meaningful learning. Therefore, the PBL-Hypnoteaching model can be considered an innovative instructional alternative for improving students' emotional well-being and mathematics learning outcomes.